2015
DOI: 10.1016/j.contraception.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of stability of polidocanol foam for nonsurgical permanent contraception

Abstract: The stability of PF is affected by the pore characteristics of the filter used for foam generation and enhanced by the presence of a small amount of BZK. The improved foam, if shown to be efficacious in animal models of contraception, could lead to a safe, simple and inexpensive method alternative to surgical contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To prepare polidocanol solution containing 0.01% BZK, we added BZK (Sigma-Aldrich 234427) to 3% stock polidocanol solution mixing overnight [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare polidocanol solution containing 0.01% BZK, we added BZK (Sigma-Aldrich 234427) to 3% stock polidocanol solution mixing overnight [9].…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that the addition of dilute (0.01%) benzalkonium chloride (BZK) (a common preservative) to polidocanol improves the stability of the resulting foam [9]. While unproven, we hypothesize that duration of foam exposure may be associated with greater tissue effects.…”
Section: Introductionmentioning
confidence: 99%
“…11 Other workers have expressed the foam onto a microscope slide to capture the images. 12 The durability measurements were made in an upturned syringe as described by others. 7,8 Liquid reformation from foams has been shown to be more rapid in vertical rather than horizontal bodies of foam 6 and drainage increases the coarsening rate of foams resulting in drier foam higher in the column.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, researchers have been working on changing the physical state of such materials and combining them with other substances in order to achieve the high contraceptive effect with significantly reduced side effects. Guo et al proposed that polidocanol were regarded as a detergent-based hardener in the form of foams rather than liquids, which can improve the contact area of the material with the epithelium, increase foam stability while reducing drug concentrations and potentially toxic epithelium-damaging activity [ 121 ]. The addition of benzalkonium chloride (BZK) has been shown to improve the stability of PF.…”
Section: Advanced Biomaterials For Contraception By Various Routesmentioning
confidence: 99%